Synthesis and anti-cancer activities of new sulfonamides 4-substituted-triazolyl nucleosides. Issue 9 (1st May 2017) - Alaoui, Soukaina; Dufies, Maeva; Driowya, Mohsine; Demange, Luc; Bougrin, Khalid; Robert, Guillaume; Auberger, Patrick; Pagès, Gilles; Benhida, Rachid
Graphical abstract: Abstract: Nucleoside analogues are among the most known drugs commonly used in antiviral and anticancer chemotherapies. Among them, those featuring a five-membered ring nucleobase are of utmost interest such as the anti-cancer agent AICAR or the anti-viral drug ribavirin. Despite its low activity in vitro in different cell lines, AICAR is under clinical development for several pathologies, thanks to its original mode of action. Indeed, AICAR induced autophagy cell death and is able, following this mechanism, to circumvent resistance to apoptotic drugs including kinase inhibitors currently on the market. To improve the activity of AICAR, we report herein an efficient synthesis of new series of sulfonamide-4-substituted-1, 2, 3-triazolyl nucleosides using a Cu-catalyzed 1, 3-dipolar cycloaddition. All these molecules have been fully characterized and evaluated against two aggressive tumor cell lines, RCC4 and MDA-MB-231. Among them, nucleoside analogue5i belonging to the ribose series was found to be 19 to 66-fold more active than AICAR. Western blot analyses on RCC4 cells showed that5i displayed an interesting mode of action by inducing both apoptosis and autophagy cell death, making therefore this class of molecules highly promising for further hit-to-lead optimization.